The study on electronic portfolios in vocational education: The views of teachers and students in United Kingdom, Denmark, Romania and Turkey - Turhan, Muhammed; Demirli, Cihad (Academic Journals, 2010)
This paper comprises teachers' and students' e-portfolio views involved in vocational education in Europe. In addition, it is a part of the final report of the project entitled E-Portfolio Process in Vocational Education within Leonardo da Vinci Procedure B Pilot project. Questionnaires were administered on 387 students and 73 teachers in Turkey, United Kingdom, Denmark, and Romania. The results suggested that both teachers and students find the e-portfolio process necessary in vocational education. The process was particularly reported to be helpful in putting theoretical knowledge to use, making use of various types of evidence for student learning, encouraging continuous student development, and actively using self-evaluation and information and computer technologies in instruction.
Keywords: Electronic portfolio; vocational education; lifelong learning